Aspects Regarding Safety and Security in Hotels: Romanian Experience - Alexandru Anichiti; Larisa-Loredana Dragolea; Georgia-Daniela Tacu Hârșan; Alina-Petronela Haller; Gina Ionela Butnaru (Information, 2021)
This study investigates safety and security from the perspective of Romanian tourists by assessing the level of importance that tourists give to safety and security depending on the level of classification of the services they experienced and the generation to which they belong. We used a quantitative research method in the form of a questionnaire and analysed eight dimensions of safety and security: detectors, emergency preparedness, medical preparedness, staff security, guestroom security, pool and beach security, hotel access control, and cyber security. We identified the differences between tourists’ perception of safety and security depending on the level of classification of accommodation services and on generation.